FOSTERING CRITICAL THINKING AND CHARACTER THROUGH PHILOSOPHY OF EDUCATION: A STUDY OF BIOLOGY PRE-SERVICE TEACHER - Reza Ma'ruf; Yundi Fitrah; Ade Kusmana Kusmana; Bunga Ayu Wulandari Wulandari (Physics and Science Education Journal (PSEJ), 2025)
This study aims to examine the influence of Philosophy of Education courses on the development of critical thinking skills and character formation among Biology Education students at UIN Sulthan Thaha Saifuddin Jambi. A descriptive quantitative research design was employed, with data collected using a Likert-scale questionnaire consisting of 17 items measuring dimensions of critical thinking skills and character development. The questionnaire was administered to 34 third-semester students who had completed the Philosophy of Education course. The findings indicate that, overall, students demonstrated high levels of critical thinking skills and character development. The mean scores for critical thinking skills encompassed information evaluation, logical reasoning, analytical thinking, and reflective thinking, with the highest mean score observed in the ability to evaluate information critically (M = 4.12). Regarding character development, students exhibited strong outcomes in moral values, including honesty, responsibility, and cooperation, with cooperation in science learning achieving the highest mean score (M = 4.35). These results suggest that Philosophy of Education courses contribute positively to enhancing students’ critical thinking skills and fostering essential character traits that support both academic achievement and social competence. The study underscores the importance of integrating Philosophy of Education into higher education curricula to equip students not only with disciplinary knowledge but also with critical thinking abilities and character development necessary for lifelong learning and societal engagement.